2017
DOI: 10.1007/s00339-017-1337-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting of hypereutectic Al-Si40-powder using ultra-short laser pulses

Abstract: We investigate the use of ultra-short laser pulses for the selective melting of Al-Si40-powder to fabricate complex lightweight structures with wall sizes below 100 μm combined with higher tensile strength and lower thermal expansion coefficient in comparison to standard Al-Si alloys. During the cooling process using conventional techniques, large primary silicon particles are formed which impairs the mechanical and thermal properties. We demonstrate that these limitations can be overcome using ultra-short las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This also agrees with literature on LPBF that indicates most metallic material, including Al-Si alloys, processed with LPBF have a finer microstructure due to the high cooling rates [48], [50]- [53]. The finer microstructure leads to a higher hardness with most materials processed by LPBF, including Al-Si alloys [186], [188], [189]. The relationship between laser exposure time or laser scanning speeds on microstructure is related to the cooling rates, a faster scanning speed will increase cooling rate, and therefore create a finer microstructure.…”
Section: Discussionsupporting
confidence: 90%
“…This also agrees with literature on LPBF that indicates most metallic material, including Al-Si alloys, processed with LPBF have a finer microstructure due to the high cooling rates [48], [50]- [53]. The finer microstructure leads to a higher hardness with most materials processed by LPBF, including Al-Si alloys [186], [188], [189]. The relationship between laser exposure time or laser scanning speeds on microstructure is related to the cooling rates, a faster scanning speed will increase cooling rate, and therefore create a finer microstructure.…”
Section: Discussionsupporting
confidence: 90%
“…2. The size of the particles was selected based on two aspects: a. the size of the spot diameter, so it can cover the maximum grain surface; b. the values found in literature, which were below 50 µm [60,62,63]. The chemical composition of these powders is presented in the following table (Table 1), which corresponds to an AISI 316L stainless steel.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the heat accumulation and melting of metal powders (such as iron [60], tungsten [60,61], copper [62] and aluminum [63]) is a feasible phenomenon when using USP lasers. These studies demonstrate that it is possible to melt various kinds of materials when laser pulses are consecutive enough, accumulating heat and increasing the temperature up to the melting threshold.…”
Section: Introductionmentioning
confidence: 99%
“…At present, due to the shortcomings of poor surface finish, low productivity, poor quality control, unrepeatability, limited component size, and limited range of printable materials, only a few AM processes are used in modern manufacturing [69]. For metal materials, various alloys have been proposed [16,70,71]. However, in actual production, the mismatch of material with different cooling rate or thermal expansion coefficient will cause many problems, such as peeling of different layers, thermal effects caused by high power, ablation of low melting point materials on the base layer, and different types problems caused by the formation and distribution of crystal images.…”
Section: Multi-materials Layered Structurementioning
confidence: 99%